SARANA BERPIKIR ILMIAH DALAM BIDANG BAHASA MATEMATIKA DAN STATISTIK - Johar Amir; Nur Apriany Nukuhaly (LPPM Politeknik Saint Paul Sorong, 2023)
To be able to do scientific thinking well requires the means of language, mathematics and statistics. The type of writing in this article is literature revieu or library nature, the data is described descriptively, thus suggesting a scientific study that can be further developed. The object of the study in this article is related to the study of the means of scientific thinking. (bahasa, matematika dan statistik). The collection of data in this paper begins with the collection of appropriate literature in both written and soft copy forms, for example textbooks, scientific articles, ebooks and so on. Both types of literature are the main source in displaying variables in this writing. The author then analyzes the data and reduces the various relevant information to eventually bring about a solution to the problems that are outlined in this article. Language is a means of communicating systematic ways of thinking in acquiring knowledge. Without language skills, one will not be able to carry out scientific activities systematically and correctly. Mathematics is a means of deductive thinking so people can use statistics to think inductive. Statistics must be viewed in parallel with mathematics